GENETIC CONTRIBUTION TO STUDENTS ACADEMIC DEVELOPMENT (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This study investigates the extent to which genetic factors influence academic achievement among students. Utilizing data from twin studies, which compare the academic performance of identical and fraternal twins, we estimate the heritability of educational outcomes. The analysis reveals that approximately 70% of the variance in academic achievement can be attributed to genetic differences, while environmental factors account for the remaining 30%. These findings underscore the significant role of genetics in shaping educational success, yet also highlight the importance of environmental influences such as family socioeconomic status and school quality. The implications of these results are profound, suggesting that while genetic predispositions play a crucial role, targeted interventions and supportive educational environments can mitigate disparities and enhance academic performance for all students. Future research should explore the interaction between genetic and environmental factors to develop more effective educational strategies.